Bitcoin Price Dynamics: The Role of Community Activity, Social Media, and Market Liquidity - Tembelo, Havane; Özyeşil, Mustafa (International Review of Management and Marketing, 2026)
This study analyze the most significant factors that influence the price of Bitcoin which is the spearhead of the cryptocurrency market. It attempts to determine the explanatory power of variables such as community activity (CA), social media impact (SM), liquidity ratio (LR), and circulating Bitcoins in the market (PS) on the Bitcoin price. Data was gathered from 06 September 2021 to 04 September 2023 on a weekly basis. Eviews 10 and Excel 2019 software were used to analyze the data after taking the logarithm of the data, which was computed through Eviews 10 and Excel 2019. In this research, time series methods such as VAR model and impulse response tests were conducted. The findings of this research indicate that the two most powerful forces driving the price of Bitcoin are the amount of social media attention it receives and the number of Bitcoins actively being traded in the market. It can also be stated that liquidity ratio has a strong effect regarding the changes in Bitcoin’s price. The least important factor in this research was community activity in comparison to all other monitored factors. The findings of the research offer new insight relevant for investors, analysts, and regulators concerning the trends and movements of the cryptocurrency market. Understanding Bitcoin better is crucial if any rational prognosis regarding the future state of the cryptocurrency market is to be made.